Fatih Akin's cinema and the new sound of Europe - Gueneli, Berna (Indiana University Press, 2019)
At a time when belonging and identity in Europe is complicated by questions of race, ethnicity, religion, and citizenship, Berna Gueneli explores the transnational works of acclaimed Turkish-German filmmaker and auteur Fatih Akın, demonstrates how Akın's aesthetics intersect with politics to reshape notions of Europe, European cinema, and cinematic history.
Keywords: Akin, Fatih, -- 1973- -- Criticism and interpretation.; Akin, Fatih, -- 1973-; Akin, Fatih -- 1973-; Bibel -- Philemonbrief; Motion picture producers and directors -- Germany -- Bibliography.; Motion pictures -- Germany -- History -- 21st century.; Motion pictures -- Europe -- History -- 21st century.; Cinéma -- Allemagne -- Histoire -- 21e siècle.; Cinéma -- Europe -- Histoire -- 21e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts.; PERFORMING ARTS -- Reference.; Motion picture producers and directors; Motion pictures; Europe; Germany; 2000-2099; Bibliographies; Criticism, interpretation, etc.; History